Anthropogenic influence on the physico-chemical parameters of Dhamra estuary and adjoining coastal water of the Bay of Bengal. (January 2021) - Swain, Sanhita; Sahu, Biraja Kumar; Pattanaik, Suchismita; Sahoo, Rajesh Kumar; Majhi, Arakshita; Satapathy, Deepty Ranjan; Panda, Chitta Ranjan; Roy, Rajdeep; Choudhury, Saroj Bandhu
Abstract: Estuaries receive the anthropogenic pollutants of their watershed area. Dhamra estuary, on the east coast of India, is such an estuary that receives a huge amount of pollutants, and it will eventually pose a threat to the ecological sensitive areas in its vicinity. Therefore, a study was carried out on physico-chemical parameters and chlorophyll- a to delineate the sources of variation during pre-monsoon and post-monsoon seasons. Surface water sampling was carried out from 12 stations in the estuarine and coastal area. Factor analysis and cluster analysis were applied to seasonal data to understand the sources of variation. From the study, it was observed that the chemical parameters are severely affected by anthropogenic influences such as sediment dredging, aquaculture effluent, and waste from industry and sewage from upstream. In the long run, this will affect the nearby nesting ground of vulnerable Olive Ridley turtles, high bio-diverse mangrove forests, and saltwater crocodile habitat. Highlights: Nutrient spikes during non-monsoon seasons indicate anthropogenic sources. The water quality is influenced by aquaculture effluents and dredging activities. Anthropogenic influence on the coastal water will affect nearby protected areas.